The Role of Listening Strategy Use in Predicting Listening Proficiency among Tenth-Grade EFL Learners - Intan Azzahra; Umar Abdullah; Fitri Alya Okta Sukma (Didascein : Journal of English Education, 2026)
Listening is a fundamental skill in EFL learning, yet many students face difficulties and show limited awareness of effective listening strategies.  This study aimed to investigate the role of listening strategy use in predicting proficiency among tenth-grade EFL learners. This study employed a correlational quantitative design with 74 tenth-grade students using convenience sampling. Data were collected using a closed-ended questionnaire to measure metacognitive, cognitive, and socio-affective strategies and a standardized TOEFL Junior listening test to assess listening proficiency. The data were analyzed using descriptive statistics, Pearson product-moment correlation, and regression analysis. The findings revealed a statistically significant positive relationship between the use of listening strategies and listening proficiency. However, the predictive power was relatively low, indicating that listening strategies contributed modestly to students’ listening performance. Among the strategy types, socio-affective strategies were used most frequently, while cognitive and metacognitive strategies were used at moderate levels. These findings suggest that although listening strategies play an important role, listening proficiency is influenced by multiple factors. In addition, factors such as learners’ motivation, prior knowledge, and exposure to English may also contribute significantly to listening achievement. Therefore, it is recommended that teachers incorporate explicit instruction of cognitive and metacognitive strategies and provide greater exposure to authentic listening materials to enhance students’ listening development.